Wykorzystanie kapitału społecznego i relacyjnego w zarządzaniu rozwojem przedsiębiorstwa - Gach, Daniel (The use social and relationship capital in the management of development of the enterprise, 2005)
In this paper the author presents the idea of the social and relationship capital. The study also handle same aspects of initiation this ideas. The author describes the benefits to be gained from application social and relationship capital.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 554-562